An Analysis of Coherence of Chinese Courtroom Discourse - Shi, Guang (International Journal of Criminology and Sociology, 2014)
Coherence, the relationships which link the meanings of utterances in a discourse or of the sentences in a text, is realized on two levels: linear or sequential coherence and global semantic structure. Taking the audio recording transcripts of two trials (one criminal and one civil) as data, this paper analyzes coherence of Chinese courtroom discourse. The findings indicate that courtroom discourse is coherent semantically (there are meaning relations between different parts of the discourse), topically (different parts of the discourse accord with its general topic), contextually (different parts of the discourse mix with the context and accomplish the communication together), and historically (the discourse refers back to its history, i.e. preceding trials, etc).